CSP transfer fluids put to the test. Issue 3 (May 2015) - Wright, Christopher Ian; Bembridge, Thomas; Wright, Edward Anthony
Abstract : IN THIS follow-up to last issue's 'Case study in CSP plant performance, ' the authors report on the results of heat transfer fluid experiments using permittivity sensors to maintain the lifetime of CSP plants.